Analysis of putative quadruplex-forming sequences in fungal genomes: novel antifungal targets? - Warner, Emily F; Bohálová, Natália; Brázda, Václav; Waller, Zoë A E; Bidula, Stefan (Microbial genomics, 2021)
Fungal infections cause >1 million deaths annually and the emergence of antifungal resistance has prompted the exploration for novel antifungal targets. Quadruplexes are four-stranded nucleic acid secondary structures, which can regulate processes such as transcription, translation, replication and recombination. They are also found in genes linked to virulence in microbes, and ligands that bind to quadruplexes can eliminate drug-resistant pathogens. Using a computational approach, we quantified putative quadruplex-forming sequences (PQS) in 1359 genomes across the fungal kingdom and explored their presence in genes related to virulence, drug resistance and biological processes associated with pathogenicity in Aspergillus fumigatus. Here we present the largest analysis of PQS in fungi and identify significant heterogeneity of these sequences throughout phyla, genera and species. PQS were genetically conserved in Aspergillus spp. and frequently pathogenic species appeared to contain fewer PQS than their lesser/non-pathogenic counterparts. GO-term analysis identified that PQS-containing genes were involved in processes linked with virulence such as zinc ion binding, the biosynthesis of secondary metabolites and regulation of transcription in A. fumigatus. Although the genome frequency of PQS was lower in A. fumigatus, PQS could be found enriched in genes involved in virulence, and genes upregulated during germination and hypoxia. Moreover, PQS were found in genes involved in drug resistance. Quadruplexes could have important roles within fungal biology and virulence, but their roles require further elucidation.
Keywords: Antifungal Agents; Fungi; transkriptom; G-quadruplexes; Drug Resistance, Fungal; Genome, Viral; virulence; Aspergillus; Transcriptome; antifungální látky; Genome, Fungal; genom fungální; Virulence; algoritmy; Aspergillus fumigatus; fungální léková rezistence; i-motifs; in-silico; Algorithms; Ascomycota; genom virový; drug resistance